The Role of Islamic Counselor in Guiding the Religious Life of Prisoners at the Purbalingga State Detention Center - Fauzah, Titi Isnaini; Martiningsih, Dwi (Proceeding International Conference on Religion, Science and Education, 2025)
The purpose of this article is to discuss the role of the Islamic Counselor in integrating religious life within the Rumah Tahanan Negara kelas IIB Purbalingga. This study employs a qualitative approach using case study methodology, focusing on the experiences of prisoners and religious counselors. The results of the research show that religious counseling through habituation to worship and studying the Qur’an, as well as advice (mauizah khasanah) has a significant impact in increasing the religious and moral understanding of inmates, as well as helping their rehabilitation process to society. The research conclude that prisoners who receive religious counseling might improve their morality and behavior, reestablish their humanity, and prepare for society by redefining their identity. In order to properly educate criminal convicts through religion counseling so that they become citizens and are well accepted by society, this research offers useful knowledge for religious counselors, policy makers, and community leaders.